Lifestyle in hypertensive subjects attending the "Academia da Cidade" program, Recife, Brazil - doi:10.5020/18061230.2011.p340 - Isabella Martins Barbosa da Silva Paes; Annick Fontbonne; Eduarda Ângela Pessoa Cesse (Universidade de Fortaleza, 2012)
Objective: To identify the lifestyle of hypertensive patients attending the "Academia da Cidade" program of the VI Sanitary District, in Recife-PE, Brazil, with regard to behaviors that can influence the control of risk factors for complications of hypertension. Methods: A descriptive, observational and cross-sectional study. The study population included all that attended the four sites of the program "Academia da Cidade"which claimed to be suffering from high blood pressure and agreed to join in the survey (n=78). Structured questionnaires were applied containing questions about social, economic and demographic factors, but also related to lifestyle. Results: Although existing a regularity in the participation and duration period of physical activity, the number of hypertensive patients who were overweight was high (n = 51, 65.4%). In relation to other behaviors, we highlight those related to eating habits, where 30 (39.2%) of interviewees were not able to identify some of these habits. Those who identified said they consumed in excess, especially fatty foods (31.3%), fried (25.0%) and meat (16.7%). Conclusion: These findings reinforce the need to develop and expand educational measures to influence behavior change of the population in relation to lifestyl